2013
DOI: 10.1038/oncsis.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 promotes dedifferentiation and imparts stem cell-like features to pancreatic cancer cells

Abstract: SOX2 (Sex-determining region Y (SRY)-Box2) has important functions during embryonic development and is involved in cancer stem cell (CSC) maintenance, in which it impairs cell growth and tumorigenicity. However, the function of SOX2 in pancreatic cancer cells is unclear. The objective of this study was to analyze SOX2 expression in human pancreatic tumors and determine the role of SOX2 in pancreatic cancer cells regulating CSC properties. In this report, we show that SOX2 is not expressed in normal pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
241
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(268 citation statements)
references
References 50 publications
18
241
3
Order By: Relevance
“…In this study, we used serum-containing medium because PANC-1 cells most rapidly form large spheres under these conditions. The spheres generated from these cells expressed high mRNA levels of CSC markers, suggesting that they contain CSCs (7,13,(17)(18)(19). A previous study showed that PANC-1 cells grown in a serum-containing medium formed clusters that were heterogeneous for dye efflux, while cells grown in the serum-free medium with supplements commonly used to culture stem cells gave rise to colonies that varied in their ability to efflux dye and respond to verapamil (27).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we used serum-containing medium because PANC-1 cells most rapidly form large spheres under these conditions. The spheres generated from these cells expressed high mRNA levels of CSC markers, suggesting that they contain CSCs (7,13,(17)(18)(19). A previous study showed that PANC-1 cells grown in a serum-containing medium formed clusters that were heterogeneous for dye efflux, while cells grown in the serum-free medium with supplements commonly used to culture stem cells gave rise to colonies that varied in their ability to efflux dye and respond to verapamil (27).…”
Section: Discussionmentioning
confidence: 98%
“…To confirm the stemness of the PANC-1 spheres, we screened the spheres for expression of CSC markers, including Oct4, sex determining region Y-box 2 (Sox2), nestin, CD24, and CD44v9 (7,(17)(18)(19). Notably, the mRNA expression level of each of these markers was higher in PANC-1 spheres than in adherent cells ( Fig.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Interestingly, strong SOX2 expression is associated with many types of human solid tumors, including lung cancer, breast cancer, ovarian carcinoma, pancreatic carcinoma and esophageal carcinoma [7] . Furthermore, recent studies have shown that SOX2 is involved in the biological behaviors of a variety of human malignancies, including proliferation [8] , apoptosis [9,10] , and invasion and metastasis [7] . In terms of CRC, the increased expression of SOX2 is associated with distant metastases and lymph-node metastases in rightsided CRC [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the short duration of iPSC generation (2-3 weeks) provides a convenient way to study mechanisms of cellular dedifferentiation, a process also associated with tumor development and metastasis (Gabbert et al, 1985;Herreros-Villanueva et al, 2013;Schwitalla et al, 2013;Zhang et al, 2013). iPSCs can be induced by ectopic expression of different sets of transcription factors, e.g.…”
Section: Introductionmentioning
confidence: 99%